FACTORS INFLUENCING THE MAINTENANCE OF STATIC AND DYNAMIC EQUILIBRIUMS (Modern American Journal of Medical and Health Sciences, 2025)
Balance beam exercises are one of the most challenging events in women's gymnastics, where maintaining body stability plays a crucial role in conditions where the ability to restore it through physical strength is extremely limited, and where the only "weapons" are precision of movement and a subtle sense of balance.